Population transfers in counter-insurgency: a recipe for success?. (3rd July 2016) - Plakoudas, Spyridon
Abstract: Since control over the population constitutes the most crucial determinant for victory in irregular warfare, how should a state authority isolate the insurgents (the "fish" in Maoist terms) from the population (the "sea" in which the "fish" thrive)? Should a state authority simply drain the "sea" by diverting its "water" elsewhere? Does the forcible transfer of the local people who support an insurgency truly work? This article studies how the royalist regime of Greece forcibly transferred thousands of villagers (over 10% of the total population) to counter the communist insurgency during the Greek Civil War (1946–1949) and shows whether and how these deportations could be crowned with success.